A, The Effect of Payroll System, Financial Incentives, Overtime Pay, and Work Environment on Employee Performance - Asmaul Khusna; Dina Fahma Sari Dina (Institut Teknologi dan Bisnis Yadika, 2026)
Increasing competition in the workplace requires companies to improve employee performance through fair payroll systems, financial incentives, overtime wages, and a supportive work environment. This study aims to analyze the influence of payroll systems, financial incentives, overtime wages, and work environment on employee performance. A quantitative approach was employed with 92 respondents. Data were collected through questionnaires and analyzed including validity, reliability, classical assumption, coefficient of determination, and hypothesis testing. The findings indicate that payroll systems, financial incentives, overtime wages, and work environment have a significant effect on employee performance, both simultaneously and partially. Financial incentives were found to be the most dominant factor influencing employee performance. Employee performance can be enhanced by optimizing financial incentives, implementing a fair and timely payroll system, providing appropriate overtime compensation, and creating a comfortable and conducive work environment